Co-pyrolysis of biomass and plastic: Circularity of wastes and comprehensive review of synergistic mechanism - Chiun Chao Seah; Chung Hong Tan; N.A. Arifin; R.S.R.M. Hafriz; A. Salmiaton; Saifuddin Nomanbhay; A.H. Shamsuddin (Results in Engineering, 2023)
Fossil fuels have provided humans with an enormous and stable primary energy source to rapidly develop advanced technologies, increasingly efficient machines and industries, as well as greater varieties of consumer products. While humans enjoy the conveniences of the modern world, critical global issues have also been created, such as an exponential hike in waste generation, rapid depletion of finite fossil fuels, greater environmental pollution, and climate change. Two major anthropogenic wastes are biomass waste and plastic waste. Each year, 464 million tonnes of plastic waste are generated globally, with only 20% recycled, 25% incinerated, while 55% landfilled. Likewise, 140 billion tonnes of biomass from the agriculture sector and 181.5 billion tonnes of lignocellulosic biomass from forestry and agricultural residues are produced worldwide annually, with only 40% and 4.5% biomass reuse respectively. This mountainous underutilised biomass and plastic wastes presented a good opportunity for recycling into biofuels instead of landfilling or open dumping, thus promoting circular bioeconomy. Pyrolysis stands out as a promising thermochemical route to synthesize biofuels, and co-pyrolysis of biomass and plastic benefits from synergistic interactions between both feedstocks, enhancing the yield and quality of biofuels. Therefore, in this review, the synergistic mechanism of biomass and plastic co-pyrolysis is described, and recent advances in this field are comprehensively presented. The importance of applying circular bioeconomy frameworks on biomass and plastic wastes are also highlighted.